Contextual factors influencing physical activity and technical performance in Australian Football League Women's competition match-play - Leabeater, A. J.; Coutts, A. J.; Clarke, A. C.: Sullivan, C. J. (The Journal of Strength and Conditioning Research, 2023)
The purpose of this study was to examine the influence of contextual factors on physical activity and technical match performance during Australian Football League Women's (AFLW) competition match-play. The study was of a retrospective longitudinal design and used physical activity and technical data collected from female Australian Football players (n = 49) from 1 team during 23 AFLW competition games over 3 seasons. A three-level linear mixed model was constructed to investigate the influence of different contextual factors (match-related variables) on relative total distance (TD), relative high-speed running (HSR) distance, and ranking points during AFLW match-play. The results showed that from season 1 to season 3, relative TD increased by 2.0 m/min (ES: 0.06 [-0.04 to 0.16], p < 0.05) and relative HSR increased by 4.1 m/min (ES: 0.22 [0.14-0.31], p < 0.001). Interstate matches were associated with a reduction of 5.1 m/min per match in TD (ES: -0.21 [-0.30 to -0.12], p < 0.001) and 2.5 m/min in HSR distance (ES: -0.22 [-0.31 to -0.13], p < 0.001). Total disposals were associated with a 0.23 m/min reduction in HSR for that player (ES: -0.13 [-0.22 to 0.04], p < 0.01). Match margin was the only contextual factor to influence ranking points/min (0.007 AU/min, ES: 0.30 [0.21-0.38], p < 0.001). In conclusion, this study shows that player physical activity may be reduced during interstate AFLW matches; the average HSR has increased since the start of the AFLW competition and may reflect increasing match activity profiles, and players have a greater rate of accumulation of ranking points when the score difference is greater.